1991
DOI: 10.2520/myco1975.1991.31
|View full text |Cite
|
Sign up to set email alerts
|

The impairing effect of chaetochromin A and related mycotoxins on mitochondrial respiration

Abstract: Chaetochromin A and related bis (naphtho-ƒÁ-pyrone) mycotoxins, cephalochromin and ustilaginoidin A, were examined for the injuring effects on mitochondrial respiration by using isolated rat liver mitochondria to gain insight into the molecular mechanism for their in vivo toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Chaetochromins A (1), B (4), C (8) and D (9) exhibited strong cytotoxicity on KB cells by inhibiting deoxyribonucleic acid, ribonucleic acid and protein biosynthesis [2]. Further mechanism of action investigations for chaetochromin A (1) revealed that the ATP synthesis in mitochondria was inhibited by uncoupling oxidative phosphorylation and depressing state-3 respiration of mitochondria, which may explain their cytotoxicity and in vivo toxicity to animals [55].…”
Section: Cytotoxic and Antitumor Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Chaetochromins A (1), B (4), C (8) and D (9) exhibited strong cytotoxicity on KB cells by inhibiting deoxyribonucleic acid, ribonucleic acid and protein biosynthesis [2]. Further mechanism of action investigations for chaetochromin A (1) revealed that the ATP synthesis in mitochondria was inhibited by uncoupling oxidative phosphorylation and depressing state-3 respiration of mitochondria, which may explain their cytotoxicity and in vivo toxicity to animals [55].…”
Section: Cytotoxic and Antitumor Activitymentioning
confidence: 99%
“…Reactive oxygen species generation and loss of the mitochondrial membrane potential (MMP) were also markedly induced by cephalochromin [18]. Cephalochromin (11) also inhibited ATP synthesis in mitochondria by uncoupling oxidative phosphorylation and depressing state-3 respiration of mitochondria [55].…”
Section: Cytotoxic and Antitumor Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Ustilaginoidins have been previously shown to have a certain toxicity and teratogenicity to embryonic limb bud and midbrain cells in mouse (Tsuchiya et al, 1987). Ustilaginoidins A was revealed to uncouple the oxidative phosphorylation, and thus, strongly inhibiting mitochondrial respiration (Kawai et al, 1991). Ustilaginoidins D and E exhibit a strong effect on mouth epidermal carcinoma cells in human by inhibiting the synthesis of DNA, RNA and proteins .…”
Section: Introductionmentioning
confidence: 99%